Methyl Jasmonate Elicitation Enhanced Biomass, Phenolic, and Flavonoid Production of Adventitious Root Culture of Gynura procumbens in Balloon Type Bubble Bioreactor - Wijayanti, Ely Tri; Kusuma, Dannis Yuda; Kristanti, Alfinda Novi; Wibowo, Anjar Tri; Sugiharto, Sugiharto; Sugiarso, Djarot; Manuhara, Yosephine Sri Wulan (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Secondary metabolites in the medicinal plant Gynura procumbens have various beneficial pharmacological activities. However, the limited availability of these beneficial compounds has constrained the possibilities for therapeutic applications. Exogenously applied methyl jasmonate (MeJa) as an elicitor has been reported to trigger the accumulation of secondary metabolites in plant tissues cultured in vitro. This study aimed to assess how varying periods of MeJa elicitation affect the growth and accumulation of phenolic and flavonoid compounds in adventitious root cultures of G. procumbens within a balloon-type bubble bioreactor (BTBB). Adventitious roots were induced from leaf and stem explants obtained from established in vitro shoots. Upon transfer to the BTBB, the cultures were supplemented with 100 µM MeJa and sampled at 1, 2, 3, and 4 weeks. The results revealed that including MeJa in the culture medium significantly boosted growth and the accumulation of phenolic and flavonoid compounds in G. procumbens. The highest biomass and concentrations of phenolic and flavonoid compounds were observed after 3 weeks of elicitation. These findings highlight the potential of MeJa elicitation for enhancing the production of valuable bioactive compounds in G. procumbens adventitious root cultures, showcasing its utility for industrial applications.